Blended Learning in Health Professions Education: A Systematic Review of Pedagogical Approaches, Digital Innovations, Learning Outcomes, and Implementation Challenges - Istiana, Mira; Siregar, Eveline; Iriani, Tuti; Rahmadi, Imam Fitri (Jurnal Paedagogy, 2026)
This study aims to examine the implementation patterns, technology integration, learning outcomes, student engagement, and sustainability factors of blended learning (BL) in health professions education (HPE) between 2020 and 2024 across diverse pedagogical and educational contexts. Despite the increasing adoption of BL in HPE, the existing literature lacks a comprehensive, theory-informed synthesis of implementation patterns, technology integration, the relationship between student engagement and learning outcomes, and sustainability factors across disciplines and educational settings. This study employed a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. The review was conducted using the Scopus database and included studies published between January 2020 and December 2024. A total of 41 peer-reviewed empirical studies were selected from an initial pool of 65 records through rigorous title and abstract screening, followed by full-text eligibility assessment. Data were synthesised narratively, and the findings were organised thematically according to five research questions using an integrated theoretical framework encompassing constructivism, cognitive load theory, multimedia learning theory, and self-regulated learning theory. The findings revealed that 58.5% of the included studies implemented general BL approaches, whereas 41.5% adopted established pedagogical frameworks. Technology integration primarily involved multimedia resources (53.7%), digital assessment platforms (43.9%), and video conferencing tools (43.9%). Overall, BL demonstrated high effectiveness, with 86% of the reported learning outcome measures indicating positive results. Structured active engagement exhibited the strongest positive association with learning outcomes (r ≈ 0.55–0.75). The main challenges included substantial resource requirements and difficulties in student self-regulation, whereas instructional design support emerged as the most important facilitating factor. These findings suggest that although BL is highly effective in HPE, its long-term sustainability depends on transitioning from ad hoc implementation to institutionally supported, theory-driven instructional design. Accordingly, educators and higher education institutions should prioritise intentional pedagogical design and sustained institutional support to ensure the effective and sustainable implementation of blended learning in health professions education.